The doorman's repose - Raschka, Christopher (New York Review children's collection., 2017)
"Some of us look up at those craggy, mysterious apartment buildings found in the posher parts of New York City and wonder what goes on inside. The Doorman's Repose collects ten stories of the doings of 777 Garden Avenue, one of the craggiest"--